Compensatory responses differ between parental tasks in a songbird species - Matteo Schiavinato; Matteo Griggio; Andrea A. Pilastro; Davide Baldan (Animal Behaviour, 2023)

Familiarity effects on fish behaviour are disrupted in shoals that contain also unfamiliar individuals - Tyrone Lucon-Xiccato; Silvia Cattelan; Matteo Griggio (Behavioral Ecology and Sociobiology, 2022)
Research on several social fishes has revealed that shoals constituted by familiar individuals behave remarkably differently compared to shoals formed by unfamiliar individuals. However, whether these behavioural changes may arise also in shoals composed by a mixture of familiar and unfamiliar individuals, a situation that may commonly occur in nature, is not clear. Here, we observed the behaviour of Mediterranean killifish ( Aphanius fasciatus ) shoals that were composed by both familiar and unfamiliar individuals (i.e. individuals were familiar to each other in pairs) and compared it with shoals entirely made by either unfamiliar or familiar individuals. Shoals formed by familiar individuals took longer to emerge from a refuge and swam more cohesively compared to shoals formed by unfamiliar fish. Shoals formed by a mixture of familiar and unfamiliar individuals behaved as shoals formed by unfamiliar individuals. Moreover, mixed shoals did not segregate in pairs according to their familiarity. This study suggests that mixed shoals do not show the behavioural effects of familiarity. Significance statement Laboratory studies have compared the behaviour of shoals formed by familiar fish versus shoals formed by unfamiliar fish, finding notable advantages in the former ones, such as improved antipredator and foraging behaviour. However, comparing these two opposite shoal types may not provide information on the natural situation, because in nature, shoals often change composition. We investigated how shoals formed by a mixture of familiar and unfamiliar fish behaved. We analysed shoals’ preference for open environment versus covers and shoals’ swimming cohesion. Results showed that shoals formed by both familiar and unfamiliar individuals mostly behave like shoals entirely formed by unfamiliar individuals. This suggests that the advantages of social groups formed by familiar fish might be hardly seen in nature for species in which shoal composition changes frequently.

Within-shoal phenotypic homogeneity overrides familiarity in a social fish - Silvia Cattelan; Matteo Griggio (Behavioral Ecology and Sociobiology, 2020)

Broad‐front migration leads to strong migratory connectivity in the lesser kestrel ( Falco naumanni ) - Maurizio Sarà; Salvatore Bondì; Ana Bermejo; Mathieu Bourgeois; Mathias Bouzin; Javier Bustamante; Javier de la Puente; Angelos Evangelidis; Annagrazia Frassanito; Egidio Fulco; Giuseppe Giglio; Gradimir Gradev; et al. (Journal of Biogeography, 2019)
Aim Migratory animals regularly move between often distant breeding and non‐breeding ranges. Knowledge about how these ranges are linked by movements of individuals from different populations is crucial for unravelling temporal variability in population spatial structuring and for identifying environmental drivers of population dynamics acting at different spatio‐temporal scales. We performed a large‐scale individual‐based migration tracking study of an Afro‐Palaearctic migratory raptor, to determine the patterns of migratory connectivity of European breeding populations. Location Europe, Africa. Methods Migration data were recorded using different devices (geolocators, satellite transmitters, Global Positioning System dataloggers) from 87 individuals breeding in the three core European populations, located in the Iberian, Italian and Balkan peninsulas. We estimated connectivity by the Mantel correlation coefficient ( r M ), and computed both the degree of separation between the non‐breeding areas of individuals from the same population (i.e. the population spread) and the relative size of the non‐breeding range (i.e. the non‐breeding range spread). Results European lesser kestrels migrated on a broad front across the Mediterranean Sea and Sahara Desert, with different populations using different routes. Iberian birds migrated to western Sahel (Senegal, Mauritania, western Mali), Balkan birds migrated chiefly to central‐eastern Sahel (Niger, Nigeria, Chad), whereas Italian ones spread from eastern Mali to Nigeria. Spatial differentiation of non‐breeding areas led to a strong migratory connectivity ( r M = .58), associated with a relatively high population (637 km) and non‐breeding range (1,149 km) spread. Main conclusions Our comprehensive analysis of the non‐breeding distribution of European lesser kestrel populations revealed a strong migratory connectivity, a rare occurrence in long‐distance avian migrants. The geographical conformation of the species’ breeding and non‐breeding ranges, together with broad‐front migration across ecological barriers, promoted the differentiation of migratory routes and non‐breeding areas. Strong connectivity could then arise because of both high population spread and broad non‐breeding range.

Familiarity and sex modulate size-dependent following behaviour in the Mediterranean killifish - Tyrone Lucon-Xiccato; Nicola Anastasia; Carlotta Mazzoldi; Matteo Griggio (The Science of Nature, 2019)

Sequence variation in melanocortin-1-receptor and tyrosinase-related protein 1 genes and their relationship with melanin-based plumage trait expression in Lesser Kestrel (Falco naumanni) males - Margherita Corti; Stefano Podofillini; Matteo Griggio; Luca Gianfranceschi; Anne-Lyse Ducrest; Alexandre Roulin; Jacopo G. Cecere; Nicola Saino; Diego Rubolini (Journal of Ornithology, 2018)

Naive tadpoles do not recognize recent invasive predatory fishes as dangerous - Attila Hettyey; Kerstin E. Thonhauser; Veronika Bókony; Dustin J. Penn; Herbert Hoi; Matteo Griggio (Ecology, 2016)
Invasive alien predators (IAP) are spreading on a global scale—often with devastating ecological effects. One reason for their success may be that prey species fail to recognize them due to a lack of co‐evolutionary history. We performed a comprehensive test of this “prey naiveté” hypothesis using a novel approach: we tested whether predator‐naive tadpoles of the agile frog ( Rana dalmatina ) display antipredator behavior upon encountering chemical cues produced by native, invasive (established or recent) or allopatric fishes (four perciforms, four siluriforms, and two cypriniforms). We studied the influence of population origin on predator‐detection ability by presenting chemical cues to predator‐naive tadpoles that originated from fishless hill‐ponds or fish‐infested floodplain populations. Before trials, we fed fishes with tadpoles or an alternative food to test whether direct chemical cues from the predator's diet influences the tadpoles’ recognition of potential predators. Tadpoles reduced their activity upon exposure to cues from native and long‐established invasive perciforms, but not in response to recent invaders, allopatric predators, or to any siluriforms. Also, predators that were previously fed with tadpoles did not universally induce behavioral defensedefenses upon first encounter. Finally, tadpoles originating from isolated hill‐ponds exhibited higher baseline activity and responded in weaker fashion than their conspecifics from floodplain populations, which co‐exist with predatory fishes. Our results indicate that tadpoles may be vulnerable to invading predatory fishes due to their inability to recognize them as dangerous, though their ability to recognize invasive IAP may evolve rapidly, in fewer than 30 generations.

Reproductive interference between Rana dalmatina and Rana temporaria affects reproductive success in natural populations - Attila Hettyey; Balázs Vági; Tibor Kovács; János Ujszegi; Patrik Katona; Márk Szederkényi; Peter B. Pearman; Matteo Griggio; Herbert Hoi (Oecologia, 2014)

The number and coloration of white flank spots predict the strength of a cutaneous immune response in female Diamond Firetails, Stagonopleura guttata - Valeria Zanollo; Matteo Griggio; Jeremy Robertson; Sonia Kleindorfer (Journal of Ornithology, 2012)

Seasonal decline of offspring quality in the European starling Sturnus vulgaris: an immune challenge experiment - Lorenzo Serra; Simone Pirrello; Manuela Caprioli; Matteo Griggio; Alessandro Andreotti; Andrea Romano; Andrea Pilastro; Nicola Saino; Roberto Sacchi; Paolo Galeotti; Mauro Fasola; Fernando Spina; et al. (Behavioral Ecology and Sociobiology, 2012)

White tail markings are an indicator of quality and affect mate preference in rock sparrows - Matteo Griggio; Francisco Valera; Alejandro Casas-Crivillé; Herbert Hoi; Andrés Barbosa (Behavioral Ecology and Sociobiology, 2011)

The effect of breeding density and male quality on paternity-assurance behaviours in the house sparrow, Passer domesticus - Herbert Hoi; Hans Tost; Matteo Griggio (Journal of Ethology, 2011)

Female ornamentation, parental quality, and competitive ability in the rock sparrow - Matteo Griggio; Valeria Zanollo; Herbert Hoi (Journal of Ethology, 2010)

Armaments and ornaments in the rock sparrow: a possible dual utility of a carotenoid-based feather signal - Matteo Griggio; Lorenzo Serra; Davide Licheri; Alessia Monti; Andrea Pilastro (Behavioral Ecology and Sociobiology, 2006)